ANALYSIS OF BIOMASS AND CARBON RESERVES IN MANGROVE ECOSYSTEM OF TRIKORA BEACH BINTAN DISTRICT RIAU ARCHIPELAGO PROVINCE MANGROVE - Febby aprilliza; Bintal Amin; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in December 2017 on mangrove ecosystem in coastal area of Trikora beach Bintan district Riau archipelago Provice. The purpose of this study was to analyze the biomass and carbon reserves of the mangrove ecosystem as well as its ability to store carbon in the mangrove ecosystem. The method used in this research is survey method and analysis using allometric equation method to calculate how big biomass and carbon reserved in mangrove ecosystem. The results of this study that average carbon produced from each station was 668.24 kg / m2 and 52.25 kg / m2 and the total carbon per hectare produced was 690.12 ton / ha and 58.05 ton / ha. Keyword: Mangrove, Carbon reserves, Biomass, Trikora Beach.